Impact of natural farming practices on growth and nutritional quality of foxtail millet (Setaria italica L.) - Harshitha, K; Yogananda, S B; Chandrakala, H; Yogesh, T C; Pravalika, K M; Sachin, M L; Theerthana, T; Divya, B; Sathisha, G S; Roopa, M N (Plant Science Today, 2026)
Natural farming practices are increasingly recognized as sustainable alternatives to chemical-intensive agriculture, offering benefits for soil health, crop productivity and nutritional quality. A field experiment spanning 2 years (2022–23 and 2023–24) was undertaken at the College of Agriculture, Vishweshwaraiah Canal (VC) Farm, Mandya, University of Agricultural Sciences, Mandya, to evaluate the effects of natural farming systems on the agronomic traits and nutritional quality of foxtail millet (Setaria italica L.). The study was laid out in a randomized complete block design (RCBD) with 12 treatments comprising liquid organic manures and microbial consortia, replicated thrice. Results revealed that the combined application of Beejamrutha (seed treatment) + Jeevamrutha at 500 L ha-1 + foliar application of 2.5 % Panchagavya + microbial consortia at 5 kg ha-1 (T12) significantly improved growth attributes, yield and quality parameters over the absolute control. Grain yield increased by approximately 70–72 % in T12 during the respective years, while straw yield improved by over 60 %. Correlation analysis indicated strong positive associations between protein content, swelling index and water absorption capacity, whereas cooking time was negatively correlated with hydration-related traits. Principal component analysis explained 59.24 % of the total variation, clearly distinguishing the superior performance of T12 compared to other treatments. Economic analysis further confirmed higher profitability with T12, achieving a benefit–cost ratio of 3.02 compared to 1.12 in control. Overall, the integration of natural farming inputs enhanced both productivity and grain quality of foxtail millet, emphasizing its potential as a sustainable strategy for resilient and nutrient-rich food production.